An Analysis of the Use of Digital Media to Enhance Junior High School Students’ Critical Thinking Skills in Solving Mathematical Problems - M Alfarisyi (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2025)
The rapid development of technology has brought various positive impacts on human life, especially in the field of education. This study aims to describe the use of interactive learning media that can influence learning outcomes of elementary school students. This research is a qualitative study using a literature review method by analyzing reliable sources, both in written form and digital formats, without direct fieldwork. Based on the analysis of several scientific articles, it was found that the use of digital learning media can improve the learning outcomes of elementary school students.Keywords: Mathematics Education, Digital Media, Critical Thinking.